Propofol Infusion Is a Feasible Bridge to Extubation in General Pediatric Intensive Care Unit - Bhalala, Utpal S.; Patel, Abhishek; Thangavelu, Malarvizhi; Sauter, Morris; Appachi, Elumalai (Frontiers in Pediatrics, 2020)
OBJECTIVE: The current literature on propofol infusion as a bridge to extubation in critically ill children is limited to children with burns and congenital cardiac disease. We hypothesize that propofol infusion is a feasible bridge to extubation in mechanically ventilated, critically ill children. DESIGN: Retrospective chart review. SETTING: Pediatric intensive care unit of a tertiary care teaching hospital. PATIENTS: Children < 21 years, admitted to our Pediatric intensive care unit (PICU), requiring mechanical ventilation (MV) for at least 48 hours and at least two sedative infusions and who received propofol infusion for 4 to 24 hours during anticipated extubation from January 2014 to May 2017. INTERVENTIONS: None MEASUREMENTS AND MAIN RESULTS: We assessed extubation success as primary outcome. We defined extubation success as no reintubation within 24 hours after extubation. We also assessed for occurrence of adverse effects of propofol infusion 1) hemodynamic instability [more than 10% change from pre-propofol baseline heart rate (HR) and mean arterial pressure (MAP) measured 4 hours before and during propofol infusion, need for any inotrope and/or fluid bolus] and 2) occurrence of lactic acidosis in absence of any documented sepsis. We compared hemodynamic parameters before and during infusion using Wilcoxon Rank Sum Test (significant p-value ≤ 0.05). We evaluated 35 critically ill, mechanically ventilated children. The median age, weight and duration of MV were 3.8 (IQR: 1.25–10.5) years, 12 (IQR: 6–16.2) kilograms and 111 (IQR: 78–212) hrs. respectively. Of the 35 patients, 15 (43%) were post-surgical (10 general and 5 cardiac) and the remaining 20 (57%) were non-surgical respiratory failure cases. The median (IQR) propofol infusion dose and duration were 64.7 (53.2-81.1) mcg/kg/min and 7.8 hrs. respectively. Only one patient got re-intubated within 24 hour of extubation and was later diagnosed with vascular ring. During propofol infusion, 7/35 (20%) patients exhibited transient drop in MAP but none had lactic acidosis or need for inotrope or fluid bolus. CONCLUSIONS: In critically ill, mechanically ventilated patients, propofol infusion used over a short duration (< 12 hours) was found to be a feasible bridge to extubation. No patient had significant hypotension or lactic acidosis during the infusion.